Promoting students’ interest through culturally sensitive curricula in higher education - Quinlan, Kathleen M.; Thomas, Dave S. P.; Hayton, Annette; Astley, Jo; Blackwood, Leda; Daramy, Fatmata K.; Duffin, Morag; Haider, Muhammad Arslan; Husbands, Deborah; Joiner, Richard; Kay, Helen; Mosoeunyane, Mary; et al. (Higher education, 2024)
Previous studies have emphasized culturally sensitive curricula in the context of enhancing minoritized students’ education. We examined the relationship between second-year higher education students’ perceptions of the cultural sensitivity of their curriculum and both majoritized and minoritized students’ interest in their course. A total of 286 (228 F) students rated the cultural sensitivity of their curriculum on six scales using a revised version of the Culturally Sensitive Curricula Scales (CSCS-R), the perceived quality of their relationships with teachers, and their interest. The CSCS-R widened the construct with two new scales and showed better reliability. Ethnic minority students ( n = 99) perceived their curriculum as less culturally sensitive than White students ( n = 182), corroborating previous findings. Black students perceived their curriculum as less culturally sensitive than Asian students. There were no significant differences between ethnic minority and White students on interest or perceived quality of relationships with teachers. Five dimensions of cultural sensitivity ( Diversity Represented , Positive Depictions , Challenge Power , Inclusive Classroom Interactions , Culturally Sensitive Assessments ) and perceived quality of relationships with teachers predicted interest. Ethnicity did not. Ensuring curricula and assessments represent diversity positively, challenge power and are inclusive may support students’ interest while reflecting an increasingly diverse society.